Seagrasses of the Philippines country report - Philippine National Seagrass Committee (Philippines Philippine National Seagrass Committee, 2004)
UNEP/GEF SCS Project: Reversing environmental degradation trends in the South China Sea and Gulf of Thailand. PNSC Publ.
Keywords: Seagrasses